Apoptosis-induced chromosome break in the AF9 gene - Cynthia Patricia, anak Nicholas (Please get the password from Digital Collection Development Unit, ext : 3932 / 3914, 2008)
Chromosomal translocations are commonly associated with leukemia. Although the results of translocation are shown to be leukaemogenic, the initial event leading to the translocation remains mainly unknown. However, it is know that the initial step of translocation is the chromosome break event. There are evidences that the apoptotic nuclease may play a role in chromosomal translocation as they are known to cleave the chromosome. Erroneous repair of these chromosomal breaks by DNA repair mechanisms may mediate chromosomal translocations. One of the genes frequently involved in chromosomal translocations in acute leukaemia is the AF9 gene. The AF9 gene is only one of the fusion partners of the MLL gene, thus the same hypothesis can be tested on other MLL fusion partner genes. It is possible that apoptosis may also play a role during chromosomal breakage in other MLL fusion partner genes too.